2021
DOI: 10.1016/j.ajo.2020.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Segment OCTA of Melanocytic Lesions of the Conjunctiva and Iris

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 43 publications
0
13
0
2
Order By: Relevance
“…Although benign iris lesions may show more organized vascular patterns compared with their malignant counterparts, there has been no consensus regarding the interpretation of angiographic findings, and therefore, the diagnostic value is uncertain. 9 The five cases in our series each presented with a different combination of the ABCDEF risk factors. Some were highly suggestive of melanoma, and others, less so.…”
Section: Discussionmentioning
confidence: 89%
“…Although benign iris lesions may show more organized vascular patterns compared with their malignant counterparts, there has been no consensus regarding the interpretation of angiographic findings, and therefore, the diagnostic value is uncertain. 9 The five cases in our series each presented with a different combination of the ABCDEF risk factors. Some were highly suggestive of melanoma, and others, less so.…”
Section: Discussionmentioning
confidence: 89%
“…(36) Although vascular patterns of the melanocytic lesions were distinct from healthy tissue, no differentiating OCTA features were found between nevi and melanoma of either the conjunctiva or iris. (37) Study showed that OCTA can be used in anterior segment ocular oncology, but better software and enhanced imaging techniques are needed before conclusions about its clinical utility can be drawn. Imaging techniques that are not dependent on light (such as ultrasound biomicroscopy, using sound waves) may be more suitable to depict tumor size.…”
Section: Diagnostic Imagingmentioning
confidence: 99%
“…A study of scleral contact lens (ScCL) wearers demonstrates that repeated use of ScCL can cause vascular alterations in conjunctiva detected by AS-OCTA ( 48 ). Recent research shows that AS-OCTA works best on superficial and non-pigmented conjunctiva lesions, and malignant lesions always accompanied by deeper and larger perilesional vessels, which could be a significant marker of clinical diagnosis ( 49 , 50 ).…”
Section: As-octa Precise Diagnosismentioning
confidence: 99%